Dinamika Sistem Hukum Tata Negara dalam Konteks Perubahan Konstitusi di Era Digital - Moh.Iqbal Nuruddin; Mochammad Rofiqul Iqbal; Zaynollah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of digital technology has significantly influenced the dynamics of the constitution and changes in constitutional law in the modern era. This article aims to provide an in-depth overview of constitutional changes that have occurred in the context of the digital era. A country's constitution acts as a legal basis that regulates the government system and the rights of its citizens. However, constitutional changes in the digital era involve new aspects that need to be carefully considered. In the digital era, the transformation of information technology has changed the way people communicate, interact and participate in the process of forming public policy. The internet and social media have become important means for individuals to convey their aspirations and influence the political decision-making process. This impact has prompted demands for constitutional changes to accommodate these new developments. Technological advances also bring new challenges related to the protection of human rights and privacy. In the digital era, safeguarding freedom of opinion, freedom of expression and access to information has become more complex. The Constitution is expected to be able to adapt to these changes to safeguard the freedom of citizens. However, constitutional changes in the digital era also present various challenges. Careful regulation is needed to achieve a balance between freedom of expression and protection against issues such as the spread of dangerous content, cybercrime and privacy violations. In this context, a deep understanding of constitutional changes in the digital era is crucial to ensure that constitutional law remains relevant and provides adequate protection in the face of continuously developing technological challenges. The process of constitutional changes in the digital era must involve broad community participation and careful consideration. wisely in order to achieve the goal of balance between technological innovation and the protection of citizens' rights. A deep understanding of the dynamics of the constitution in the digital era is very important to maintain the sustainability, relevance and effectiveness of the constitution in facing the reality of dynamic technological developments.